Distributed networked control system for power supply system of the accelerator based on CANopen protocol - Chepurnov, A.S.; Gribov, I.V.; Matveev, N.V.; Belogorskiy, K.A.; Nedeoglo, F.N. (Вопросы атомной науки и техники, 2006)
Network-based control system for a power supply unit of the linear accelerator was developed. Front-end level of the system is based on CAN fieldbus with CANopen and CANEX application level protocols. Both local and remote control for each CANopen node is provided. Level 2 control stations of the system are ARM9 CPU based machines, operating under Linux OS.